Validitas Pengembangan Modul Pembelajaran Fisika Berbasis Etnosains Wisata Pantai Bangsring Underwater Untuk Meningkatkan Kemampuan Literasi Sains Siswa SMA - Agustina, Linda; Bachtiar, Rayendra Wahyu; Hana, Bea (Jayapangus Press, 2025)
This study aims to describe the validity of the Bangsring Underwater Tourism Ethnoscience-Based Physics Learning Module and its effect on high school students' science literacy skills. Research and development used the 4D model. Data were collected using validity instruments and then analyzed descriptively. The module validity research instrument had 7 assessment indicators, namely construct, language, content feasibility, presentation feasibility, science literacy elements, ethnoscience elements, and module elements. The research subjects were three lecturers who were experts in science education. The results of the instrument assessment by expert lecturers were validated using Aikens' V formula. The validity results showed that the Bangsring Underwater Ethnoscience-Based Module met the “highly valid” category with an average percentage of 91.5%. The Bangsring Underwater Ethnoscience-Based Physics Learning Module was declared highly valid for improving the science literacy skills of high school students.